A Comparison of Fosaprepitant and Ondansetron for Preventing Postoperative Nausea and Vomiting in Moderate to High Risk Patients: A Retrospective Database Analysis. (19th December 2017) - Murakami, Chiaki; Kakuta, Nami; Kume, Katsuyoshi; Sakai, Yoko; Kasai, Asuka; Oyama, Takuro; Tanaka, Katsuya; Tsutsumi, Yasuo M.
Abstract : Postoperative nausea and vomiting (PONV) occur in 30–50% of patients undergoing general anesthesia and in 70–80% of high PONV risk patients. In this study, we investigated the efficacy of fosaprepitant, a neurokinin-1 (NK1) receptor antagonist, compared to ondansetron, a selective 5-hydroxytryptamine type 3 (5-HT3) receptor antagonist, in moderate to high PONV risk patients from our previous randomized controlled trials. Patients (171 patients from 4 pooled studies) with the Apfel simplified score ≥ 2 and undergoing general anesthesia were randomly allocated to receive intravenous fosaprepitant 150 mg (NK1 group, n = 82 ) and intravenous ondansetron 4 mg (ONS group, n = 89 ) before induction of anesthesia. Incidence of vomiting was significantly lower in the NK1 group compared to the ONS group 0–2, 0–24, and 0–48 hours after surgery (2 versus 17%, 2 versus 28%, and 2 versus 29%, resp.). However, no significant differences in PONV, complete response, rescue antiemetic use, and nausea score were observed between groups 0–48 hours after surgery. In moderate to high PONV risk patients, fosaprepitant decreased the incidence of vomiting and was superior to ondansetron in preventing postoperative vomiting 0–48 hours after surgery.